SCREENING OF SOME INDIAN HOUSEHOLD SPICES FOR COMPARATIVE STUDIES OF ANTIOXIDANT AND ANTIRADICAL ACTIVITIES BY USING IN-VITRO MODELS - Phatak, Rohan Sharadanand; Krishnaji, Asha; Subhash, Anup (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â Background: India is endowed with enormous varieties of spices grown in the majority of the country and one of the largest exporters of spices in the world. Many household spices are being used integrally in the Indian foods. Spices are normally added in the food to impart flavor. They are naturally occurring antioxidants, which have the potential capacity to counteract aging process in the body, to stabilize the cell membrane by scavenging free radicals in small doses. Objectives: The current study was designed to determine antioxidant potential of some selected spices and their mixture based on the established scientific evidences and oxygen radical absorbance capacity values using different in vitro models and correlating. Methods: The powder of assigned spices and their mixture were alcoholically extracted by a simple maceration method. They were evaluated for their total phenolic and flavonoid contents. Antioxidative abilities of the extracts of spices individually and their mixtures extracts were analyzed by phosphomolybdenum assay, cupric ions reducing antioxidant capacity (CUPRAC) and ferric ions reducing ability power methods. The free radical scavenging activities such as hydrogen peroxide, ABTS, anti-peroxidation like TBARS (thiobarbituric acid reactive substance), crocin bleaching and metal chelation capacity were assayed through in vitro models. Results and Discussion: Antioxidant and antiradical effects of the selected spices extracts and spices mixture extract (SME) was ascertained through different in vitro models. Results of individual tests demonstrated good correlation among themselves. CUPRAC has strong correlation with all other assays except to diphenyl-1-picrylhydrazyl (DPPH) and thiobarbituric acid reactive substances (TBARS). DPPH and TBARS were correlated with each other however they demonstrated no relationship with other assays. Conclusion: Extracts of selected Indian spices extracts and SME have shown dissimilarity to each other. Study for the 1st time establishes aggregate index for evaluation of Indian spices. On basis of aggregate index, nutmeg has highest value among the selected spices and no significant synergistic effect has been found in SME. CUPRAC as antioxidant assay and hydroxyl free radical scavenging assay by using Smirnoff reagent are most appropriate assays to ascertain antioxidative and free scavenger properties of natural products. Keywords: Antioxidants, Antiradical, Oxygen Radical Absorbance Capacity, Spices, Spices Mixture Extract.